Constant relative risk aversion and form equivalence classes - Harald L. Battermann; Udo Broll; Jack E. Wahl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
We derive a class of utility functions that are equivalent with respect to a well-defined functional form. We apply a general view of constant relative risk aversion to investigate on different equivalence relations. Then we compare our results with standard applications in economics and finance.
Keywords: D81; D11; G11; 330; risk aversion; equivalence class; utility theory; Nutzenfunktion; Risiko; Theorie